2022
DOI: 10.17161/kjm.vol15.15699
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Involvement as a Predictor of Mortality in COVID-19 Patients in a Safety Net Hospital

Abstract: Introduction. COVID-19 affects the hematologic system. We evaluate the impact of hematologic involvement of different blood cell line parameters of white blood cells including absolute neutrophil count (ANC), hemoglobin, and platelets in COVID-19 patients and their association with hospital mortality and length of stay (LOS).  Methods. This is a retrospective study of 475 patients with confirmed positive COVID-19 infection and hematologic abnormalities in the metropolitan New York City area. Results. Increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Regulatory mechanisms of neutrophil activation and changes in lung function continue to be the subject of active study [ 25 ]. Increased levels of neutrophils in the circulating blood are one of the most important signs of inflammation in COVID-19 [ 68 , 69 , 70 ]. Thus, an increase in the level of these cells in the circulation in conjunction with some other routine clinical tests allows us to distinguish patients in critical condition from patients with a severe course of the disease already in the early stages of the development of infection.…”
Section: Immunologic Features Of Bronchial Asthma Developmentmentioning
confidence: 99%
“…Regulatory mechanisms of neutrophil activation and changes in lung function continue to be the subject of active study [ 25 ]. Increased levels of neutrophils in the circulating blood are one of the most important signs of inflammation in COVID-19 [ 68 , 69 , 70 ]. Thus, an increase in the level of these cells in the circulation in conjunction with some other routine clinical tests allows us to distinguish patients in critical condition from patients with a severe course of the disease already in the early stages of the development of infection.…”
Section: Immunologic Features Of Bronchial Asthma Developmentmentioning
confidence: 99%
“…Recent studies have observed a significant rise in neutrophil count among patients with COVID-19 [ 5 , 14 , 15 ]. Chen et al [ 16 ] reported that severe or critical COVID-19 patients had notably higher neutrophil counts upon admission than mild/moderate COVID-19 patients.…”
Section: Neutrophils and Covid-19mentioning
confidence: 99%
“…Early hematological abnormalities in COVID-19 patients have also been associated with an elevated risk of mortality [8,9]. As for the hematological changes that may reflect the high severity, studies have shown that platelet counts, leukocytes, lymphocytes, hemoglobin, acute phase proteins such as ferritin and C-reactive protein, in addition to irregularities in the elements of coagulation cascade and fibrin degradation products such as D-dimer, were found in patients with severe COVID-19, as well as being associated with disease progression [10,11].…”
Section: Hematological Alterations In Covid-19mentioning
confidence: 99%